Pd/C-catalyzed aerobic oxidative esteriﬁcation of alcohols and aldehydes: a highly efficient microwave-assisted green protocol - Caporaso, Marina; Cravotto, Giancarlo; Georgakopoulos, Spyros; Heropoulos, George; Martina, Katia; Tagliapietra, Silvia (Beilstein Journal of Organic Chemistry, 2014)
We herein describe an environmentally friendly microwave-assisted oxidative esteriﬁcation of alcohols and aldehydes in the presence of molecular oxygen and a heterogeneous catalysis (Pd/C, 5 mol %). This efficient and ligandless conversion procedure does not require the addition of an organic hydrogen acceptor. The reaction rate is strongly enhanced by mild dielectric heating. Furthermore, it is a versatile green procedure which generally enables the isolation of esters to be carried out by simple filtration in almost quantitative yields.
Keywords: aerobic oxidation; alcohol; esterification; heterogeneous catalysis; microwaves

(untitled) - Mallat, T.; Baiker, A. (Chem. Rev., 2004)

(untitled) - Matsumoto, T.; Ueno, M.; Wang, N.; Kobayashi, S. (Chem.–Asian J., 2008)

(untitled) - Davis, S. E.; Ide, M. S.; Davis, R. J. (Green Chem., 2013)

(untitled) - Karimia, B.; Esfahani, F. K. (Adv. Synth. Catal., 2012)

(untitled) - Su, F.-Z.; Liu, Y.-M.; Wang, L.-C.; Cao, Y.; He, H.-Y.; Fan, K.-N. (Angew. Chem., Int. Ed., 2007)

(untitled) - Mitsudome, T.; Noujima, A.; Mizugaki, T.; Jitsukawa, K.; Kaneda, K. (Adv. Synth. Catal., 2009)

(untitled) - Lucchesi, C.; Inasaki, T.; Miyamura, H.; Matsubara, R.; Kobayashi, S. (Adv. Synth. Catal., 2008)

(untitled) - Mahyari, M.; Shaabani, A.; Bide, Y. (RSC Adv., 2013)

(untitled) - Mori, K.; Hara, T.; Mizugaki, T.; Ebitani, K.; Kaneda, K. (J. Am. Chem. Soc., 2004)

(untitled) - Karimi, B.; Abedi, S.; Clark, J. H.; Budarin, V. (Angew. Chem., Int. Ed., 2006)

(untitled) - Dun, R.; Wang, X.; Tan, M.; Huang, Z.; Huang, X.; Ding, W.; Lu, X. (ACS Catal., 2013)

(untitled) - Chen, G.; Wu, S.; Liu, H.; Jiang, H.; Li, Y. (Green Chem., 2013)

(untitled) - Yamaguchi, K.; Mori, K.; Mizugaki, T.; Ebitani, K.; Kaneda, K. (J. Am. Chem. Soc., 2000)

(untitled) - Yamaguchi, K.; Mizuno, N. (Angew. Chem., Int. Ed., 2002)

(untitled) - Yu, H.; Wu, Y.; Peng, F.; Zhang, Y.; Wang, H.; Yang, J. (Catal. Lett., 2012)

(untitled) - Costa, V. V.; Jacinto, M. J.; Rossi, L. R.; Landers, R.; Gusevskaya, E. V. (J. Catal., 2011)

(untitled) - Shiraishi, Y.; Sakamoto, H.; Sugano, Y.; Ichikawa, S.; Hirai, T. (ACS Nano, 2013)

(untitled) - Suvendu, S.; Das, S.; Partha Kumar, S.; Supriya, D.; Papu, B. (RSC Adv., 2013)

(untitled) - Chen, L.; Hu, J.; Sankar Mal, S.; Kortz, U.; Jaensch, H.; Mathys, G.; Richards, R. M. (Chem.–Eur. J., 2009)

(untitled) - Dobereiner, G. E.; Crabtree, R. H. (Chem. Rev., 2010)

(untitled) - Oliveira, R. L.; Kiyohara, P. K.; Rossi, L. M. (Green Chem., 2009)

(untitled) - Miyamura, H.; Yasukawa, T.; Kobayashi, V. (Green Chem., 2010)

(untitled) - Su, F.-Z.; Ni, J.; Sun, H.; Cao, Y.; He, H.-Y.; Fan, K.-N. (Chem.–Eur. J., 2008)

(untitled) - Ishida, T.; Nagaoka, M.; Akita, T.; Haruta, M. (Chem.–Eur. J., 2008)

(untitled) - Kaizuka, K.; Miyamura, H.; Kobayashi, S. (J. Am. Chem. Soc., 2010)

(untitled) - Tang, L.; Guo, X.; Li, Y.; Zhang, S.; Zha, Z.; Wang, Z. (Chem. Commun., 2013)

(untitled) - Zhang, J.; Leitus, G.; Ben-David, Y.; Milstein, D. (J. Am. Chem. Soc., 2005)

(untitled) - Owston, N. A.; Parkerb, A. J.; Williams, J. M. J. (Chem. Commun., 2008)

(untitled) - Zhang, D.; Pan, C. (Catal. Commun., 2012)

(untitled) - Yamamoto, N.; Obora, Y.; Ishii, Y. (J. Org. Chem., 2011)

(untitled) - Gowrisankar, S.; Neumann, H.; Beller, M. (Angew. Chem., Int. Ed., 2011)

(untitled) - Liu, C.; Wang, J.; Meng, L.; Deng, Y.; Li, Y.; Lei, A. (Angew. Chem., Int. Ed., 2011)

(untitled) - Bai, X.-F.; Ye, F.; Zheng, L.-S.; Lai, G.-Q.; Xia, C.-G.; Xu, L.-W. (Chem. Commun., 2012)

(untitled) - Liu, C.; Tang, S.; Lei, A. (Chem. Commun., 2013)

(untitled) - Luo, F.; Pan, C.; Cheng, J.; Chen, F. (Tetrahedron, 2011)

(untitled) - Sheldon, R. A.; Arends, I. W. C. E.; ten Brink, G.-J.; Dijksman, A. (Acc. Chem. Res., 2002)

(untitled) - Parmeggiani, C.; Cardona, F. (Green Chem., 2012)

(untitled) - Stahl, S. S. (Angew. Chem., Int. Ed., 2004)

(untitled) - Muzart, J. (Tetrahedron, 2003)

(untitled) - Powell, A. B.; Stahl, S. S. (Org. Lett., 2013)

(untitled) - Jagadeesh, R. V.; Junge, H.; Pohl, M.-M.; Radnik, J.; Brückner, A.; Beller, M. (J. Am. Chem. Soc., 2013)

(untitled) - Wang, N.; Matsumoto, T.; Ueno, M.; Miyamura, H.; Kobayashi, S. (Angew. Chem., Int. Ed., 2009)

(untitled) - Korovchenko, P.; Donze, C.; Gallezot, P.; Besson, M. (Catal. Today, 2007)

(untitled) - Heropoulos, G. A.; Villalonga-Barber, C. (Tetrahedron Lett., 2011)

(untitled) - Muzart, A.; Zeltner, M.; Stark, W. J. (ACS Catal., 2012)

(untitled) - Cravotto, G.; Beggiato, M.; Palmisano, G.; Penoni, A.; Lévêque, J.-M.; Bonrath, W. (Tetrahedron Lett., 2005)

(untitled) - Tagliapietra, S.; Cravotto, G.; Calcio Gaudino, E.; Visentin, S.; Mussi, V. (Synlett, 2012)

Microwaves in Organic Synthesis - De La Hoz, A.; Loupy, A. (Springer, 2012)

(untitled) - Barge, A.; Tagliapietra, S.; Tei, L.; Cintas, P.; Cravotto, G. (Curr. Org. Chem., 2008)

(untitled) - Palmisano, G.; Bonrath, W.; Boffa, L.; Garella, D.; Barge, A.; Cravotto, G. (Adv. Synth. Catal., 2007)

(untitled) - Kaval, N.; Dehaen, W.; Kappe, O. C.; Van der Eycken, E. (Org. Biomol. Chem., 2004)

(untitled) - Will, H.; Scholz, P.; Ondruschka, B. (Chem. Ing. Tech., 2002)

(untitled) - Tanner, D. D.; Kandanarachchi, P.; Ding, Q.; Shao, Q.; Vizitiu, D.; Franz, J. A. (Energy Fuels, 2001)

(untitled) - Zhang, X.; Lee, C. S.-M.; Mingos, D. M. P.; Hayward, D. O. (Catal. Lett., 2003)

(untitled) - Zhang, X.; Hayward, D. O.; Mingos, D. M. P. (Catal. Lett., 2003)

(untitled) - Carnaroglio, D.; Martina, K.; Palmisano, G.; Penoni, A.; Domini, C.; Cravotto, G. (Beilstein J. Org. Chem., 2013)

(untitled) - Modak, A.; Deb, A.; Patra, T.; Rana, S.; Maity, S.; Maiti, D. (Chem. Commun., 2012)

(untitled) - Akanksha; Maiti, D. (Green Chem., 2012)

(untitled) - Sergeev, A. G.; Neumann, H.; Spannenberg, A.; Beller, M. (Organometallics, 2010)